2021
DOI: 10.1186/s12912-021-00716-x
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of a complex workplace intervention to prevent musculoskeletal pain in nursing staff: results from INTEVAL_Spain

Abstract: Background INTEVAL_Spain was a complex workplace intervention to prevent and manage musculoskeletal pain among nursing staff. Process evaluations can be especially useful for complex and multifaceted interventions through identifying the success or failure factors of an intervention to improve the intervention implementation. Objectives This study performed a process evaluation of INTEVAL_Spain and aimed to examine whether the intervention was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…Perhaps we would have found an effect on quality-adjusted life years by comparing baseline data with the 12months follow-up. Third, effectiveness results could have been limited by the process implementation, as the intervention had a slightly lower implementation than expected [47]. Recommendations to improve the implementation have been published…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps we would have found an effect on quality-adjusted life years by comparing baseline data with the 12months follow-up. Third, effectiveness results could have been limited by the process implementation, as the intervention had a slightly lower implementation than expected [47]. Recommendations to improve the implementation have been published…”
Section: Limitationsmentioning
confidence: 99%
“…elsewhere [47]. Finally, other information regarding costs and effectiveness might be missing, as no information was available on whether nursing staff consumed over-the-counter medication, or whether they went to private hospitals or services (e.g., physiotherapy consultations, etc.…”
Section: Limitationsmentioning
confidence: 99%
“…In addition, we will use both quantitative and qualitative methods, which can give a wider understanding of the feasibility of NW for patients, permitting analysing also the experience of participants with the exercise program. To our knowledge, this is the second study planning a focus group evaluation of NW training [70], and the third study approaching any qualitative study method, taking in account focus groups [71].…”
Section: Strengthens and Weaknessesmentioning
confidence: 99%
“…Además, aportó información importante sobre indicadores de proceso que podrían ser de utilidad para futuras implementaciones de esta intervención o similares. Se concluyó que era necesaria la flexibilidad en cuanto al calendario y horarios, tanto en la fase de reclutamiento de participantes, como en la fase de intervención (12) . En este aspecto, se consideró que realizar reuniones informativas en cada una de las unidades hospitalarias participantes y en los diferentes turnos, habría facilitado la asistencia de los trabajadores y habría podido facilitar el reclutamiento.…”
Section: Inteval Un Ejemplo De Intervención Efectiva Para El Dolor Os...unclassified
“…Furthermore, it provided important information on process indicators that could be useful for future implementations of this or similar interventions. It was concluded that there was a need for flexibility in terms of timing and scheduling, both in the recruitment phase and during the intervention (12) . In this regard, holding information meetings in each of the participating hospital units and on different shifts would have facilitated workers' participation and could probably have increased recruitment.…”
mentioning
confidence: 99%